Obscuring Gender-Based Violence: Marriage Promotion and Teen Dating Violence Research. (2nd January 2016) - Baker, Carrie; Stein, Nan
Abstract: This article argues that United States public policies have prioritized marriage and healthy relationship promotion over research and education about gendered violence in teen dating relationships, despite evidence of the prevalence of intimate partner and teen dating violence that disproportionately impacts women and girls. The lack of a gender-based analysis reflects a shift from a feminist framing of violence that focuses on the safety and well-being of women and girls based on an analysis of gender, power, and structural inequalities, toward a conservative focus on individualistic solutions to gendered social problems like poverty and violence.